Synthesis - Jacquet F.; Lerin F. (The GATT and Mediterranean agricultural trade, 1997)
This synthesis on 'the GATT and Mediterranean agriculture trade' seminar reviews the principal results of the work of this seminar. From the point of view of the Mediterranean countries, the consequences of the GATT on their economies are seen differently according to the country and, in particular, according to their agricultural trade balances. For the European Mediterranean countries (Spain, France, Greece, Italy, Portugal) the final act of the GATT forces them to face greater competition than previously in the international markets, and thus to restructure their agriculture. In the case of third Mediterranean countries, certain effects are identical for all, such as the increase of imports of basic products. On the other hand, the overall impact on exported products depends on the situation of the country and its capacity to adapt. One of the major constraints appears to be the difficulty of managing the transitory period.
Séminaire sur 'Le GATT et les Echanges Agricoles Méditerranéens', 1995/12/03-05, Chania (Greece)